An international study of the quality of life of adult patients treated with home parenteral nutrition. Issue 4 (August 2019) - Baxter, Janet P.; Fayers, Peter M.; Bozzetti, Federico; Kelly, Darlene; Joly, Francisca; Wanten, Geert; Jonkers, Cora; Cuerda, Cristina; van Gossum, Andre; Klek, Stanislaw; Boudreault, Marie-France; Gilbert, Alain; et al.
Summary: Background & aims: Home parenteral nutrition-quality of life (HPN-QOL © ) is a self-assessment tool for the measurement of QOL in patients on HPN. The aims of this study were: to re-assess the basic psychometric properties of the HPN-QOL © in a multinational sample of adult patients; to provide a description of QOL dimensions by short and long HPN treatment duration; to explore clinical factors potentially associated to QOL scores. Methods: Patients (n = 699) from 14 countries completed the HPN-QOL © . The questionnaires were analysed to evaluate data completeness, convergent/discriminant validity and internal-consistency reliability. The association of overall QOL and HPN treatment duration as well as other clinical factors were investigated using multivariable linear regression models. Results: The analysis of the multitrait-scaling and internal consistency indicates a good fit with the questionnaire structure for most items. Item discriminant validity correlation was satisfactory and psychometric evaluation of the HPN-QOL © in the different English, French and Italian language patient sub-groups confirmed psychometric equivalence of the three questionnaire versions. The results of the multivariable linear regression showed that QOL scores were significantly associated with HPN duration (better in long-term), underlying disease (better in Crohn's disease and mesenteric ischaemia) and living status (worse in living alone) and, after adjusting for the other factors, with the number of days of HPN infusion per week. Conclusions: The HPN-QOL ©, is a valid tool for measurement of QOL in patients on HPN, to be used in the clinical practice as well as in research.